The "Crystal Growth" of sustainable regional development - The example of the Lake Constance Agenda 21 - Manfred Walser; Roland Scherer (European Regional Science Association (ERSA), 2002)
Implementing sustainable regional development by institutionalising a structure of responsibility can be compared with originating the growth of a crystal by introducing a nucleus in a chemical solution. This is the result of a top down initiated regional Agenda 21-process in the international Lake of Constance- region. The interplay between top down and bottom up activities as a precondition of success of regional development is part of the theoretical mainstream. But how the interplay will work en detail often can be supposed as the 'black hole' of the theory. In most cases the interplay is described as a kind of public and private - partnership. The public activities are referred to as the 'top down' -part of the co-operation and the social activities are seen as the bottom up- level of the partnership. But much more than the dualism between private and public activities the principle of subsidiarity determines the regional networking as the bottom up- level has to be seen as a conglomerate of public and private activities. There are no simple explanations of how the different levels within the public administration work together. In our case the actors on a higher political level started a process of diffusion of tasks and responsibilities: 1. The International Conference of the heads of government of the Lake of Constance -Region (IBK) started the regional Agenda 21 with a preliminary survey on the adequate topics and procedures. 2. As a second step the main focus was on networking also initiated from top down. Within this first annual focus the responsible 'group of governance' of the process of sustainable regional development realised the necessity of a regional based working structure. 3. In a third step they introduced a network of responsible actors within the public administration by sponsoring the subregions with complementary resources out of the EU's INTERREG III- Programme of transborder cooperation. This kind of 'institutionalizing from top down' was authorized by the subregional heads of government. And now the growing of the crystals has started. Originally the responsibility for the new task was dedicated to the executives of the respective departement of environment in each subregion. During one year the task trickled through institutions and instances, until the responsibility met the adequate actor. The term 'adequate' in this case means a combination between institutional setting, personal qualification and commitments as well as the dominating political bias within the subregion. The paper shows the different solutions found in the thirteen subregions of the Lake of Constance -region according to the respective situation. Further on it describes the different self-images and modes of performing the tasks. Based on the results of the empirical observation personal and institutional requirements on a network of actors for sustainable regional development can be formulated.
Keywords: 330